THE INFLUENCE OF ASPHALT RESIN PARAFFIN OIL RESIDUE ON ASPHALT CONCRETE TECHNOLOGY - Bisenov Kylyshbai Aldabergenovich; Tanzharikov Panabek Absatovich; Sarabekova Ulbosyn Zhangabylkyzy (Academic Scientific Journal of Chemistry, 2020)
Based on scientific research and experimental tests, it has been proved that solid waste from oil fields in the Kyzylorda region based on asphalt resin paraffin sediment (ARPS) is close and binding in its chemical composition to the main component of the asphalt-concrete mixture of the road surface. And the most effective method of disposal and neutralization of oil waste was chosen. The ARPS formed from the use of oil at the Kumkol field was studied, which includes asphaltenes 3 ... 8%; resins-13 ... 20%; fats-34...65%; mechanical impurities-20...49%; water-1...5%. In this article, it is proposed to develop an asphalt-concrete technology based on asphalt-resinous paraffin deposits. The issue of increasing the reserves of raw materials for the production of durable asphalt concrete and reducing the amount of oil-containing waste in the fields due to the sale of solid oil-containing waste will be considered. Based on the study, the composition of asphalt-resinous paraffin deposits was analyzed by IR spectroscopy. The infrared (IR) absorption spectrum was captured in the IR-Fourier spectrometer IR Prestige-21. The absorption spectra of asphalt-tar-paraffin deposits recorded by the IR spectrometer show the structure of hydrocarbons in the methyl (2954-2852 cm-1), methylene (1463-1377 cm-1), and methine (721 cm-1) groups. The analysis shows that the composition of solid oil waste generated at the fields consists mainly of paraffin hydrocarbons. The results of the study showed the suitability of asphalt-resinous paraffin deposits for use as organic binders to dense asphalt concrete of type" B " grade III for IV-V road climatic zones recommended for applying top layers of coating on roads of technical category IY. Replacing scarce commercial bitumen with oil waste will significantly reduce the cost of commercial products, as well as simplify the process of preparing the mixture and prevent environmental pollution with harmful substances released from oil.